Clinic Attendance for Medication Refills and Medication Adherence amongst an Antiretroviral Treatment Cohort in Uganda: A Prospective Study - Setor Kunutsor; John Walley; Elly Katabira; Simon Muchuro; Hudson Balidawa; Elizabeth Namagala; Eric Ikoona (AIDS Research and Treatment)
Background. Regular clinic attendance for antiretroviral (ARV) drug refills is important for successful clinical outcomes in HIV management. Methods. Clinic attendance for ARV drug refills and medication adherence using a clinic-based pill count in 392 adult patients receiving antiretroviral therapy (ART) in a district hospital in Uganda were prospectively monitored over a 28-week period. Results. Of the 2267 total scheduled clinic visits, 40 (1.8%) were missed visits. Among the 392 clients, 361 (92%) attended all appointments for their refills (regular attendance). Clinic attendance for refills was statistically significantly associated with medication adherence with regular attendant clients having about fourfold greater odds of achieving optimal (≥95%) medication adherence [odds ratio (OR)=3.89, 95% CI: 1.48 to 10.25, exact P=.013]. In multivariate analysis, clients in age category 35 years and below were less likely to achieve regular clinic attendance. Conclusion. Monitoring of clinic attendance may be an objective and effective measure and could be a useful adjunct to an adherence measure such as pill counting in resource-constrained settings. Where human resource constraints do not allow pill counts or other time-consuming measures, then monitoring clinic attendance and acting on missed appointments may be an effective proxy measure.